Guide to antimicrobial therapy in the adult ICU 2012 - Chan, Louisa; Mat Nor, Mohd Basri; Ibrahim, Noor Airini; Rudra Deva, Shanti; Tai, Li Ling (Malaysian Society of Intensive Care, MSIC secretariat, 2012)
Sepsis still remains one of the commonest cause of ntensive care admission here in Malaysia. In the last six years following the first edition, there has been burgeoning increase in knowledge and usage of antimicrobials. However the pressing issues of growing antimicrobial resistance, inappropriate therapy and escalating cost compel for a more responsible prescriber. In order to keep pace with important advances, most chapters have been revised and others eliminated. The objective of this book has not strayed from its original purpose that is to provide a quick and comprehensive guide for the Malaysian doctors caring for the critically ill. The structure has been kept to facilitate easy bedside referencing. The notations have expanded to explain the rationale behind antibiotic choices. Hence we hope this handbook will add to the armamentarium of those who work in intensive care units. The first revision of the ‘The MSA Guide to Antimicrobial Therapy in the Adult ICU’ has been assumed by the Malaysian Society of Intensive Care. This guide has been a culmination of many hours of evidence review and exchange of opinions. Putting it together to cater to our local needs have been a challenge for us. We would like to thank our external reviewers for their invaluable input and also acknowledge the contribution of the working committee of the first edition: it is on the foundation of their work that the present,Second edition has been developed.